2021
DOI: 10.1016/j.jopan.2020.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Using Guided Imagery to Relieve the Anxiety of Preschool Children Undergoing Dental Procedures

Abstract: Purpose: Negative experiences in dental clinics can induce anxiety in patients, and the effects are particularly pronounced in children. When behavior guidance methods (eg, direct observation, tell-show-do, and ask-tell-ask) fail, general anesthesia is an important alternative; however, the procedure of anesthesia can also induce fear and anxiety. This study assessed the effectiveness of guided imagery in relieving the anxiety associated with dental surgery in children and caregivers. Design: A prospective ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…This might be explained by the fact that virtual reality application might help children and their parents to calm down, feel less panicky, and spend less time in counseling. This finding is in line with findings from Fincher et al (2012) and Ko et al (2021), who found that it is thought that between 50 and 70 percent of hospitalized children feel extreme anxiety and anguish before surgery. A similar conclusion was made by Nisha and Umarani (2013), who focused on the fact that children are more susceptible to anxiety and examined the impact of play interventions on the alleviation of anxiety in preoperative children.…”
Section: Discussionsupporting
confidence: 91%
“…This might be explained by the fact that virtual reality application might help children and their parents to calm down, feel less panicky, and spend less time in counseling. This finding is in line with findings from Fincher et al (2012) and Ko et al (2021), who found that it is thought that between 50 and 70 percent of hospitalized children feel extreme anxiety and anguish before surgery. A similar conclusion was made by Nisha and Umarani (2013), who focused on the fact that children are more susceptible to anxiety and examined the impact of play interventions on the alleviation of anxiety in preoperative children.…”
Section: Discussionsupporting
confidence: 91%